Evidence-based objective performance criteria for the evaluation of hip and knee replacement devices and technologies - Nieuwenhuijse, Marc J.; Randsborg, Per-Henrik; Hyde, Jensen H.; Xi, Wenna; Franklin, Patricia; Sun, Limin; Zheng, Xinyan; Banerjee, Samprit; Mao, Jialin; Aryal, Suvekshya; Chan, Priscilla; Chen, Amanda; et al. (International journal of surgery (London, England), 2023)
Objective performance criteria (OPC) is a novel method to provide minimum performance standards and improve the regulated introduction of original or incremental device innovations in order to prevent patients from being exposed to potentially inferior designs whilst allowing timely access to improvements. We developed 2-year safety and effectiveness OPC for total hip and knee replacement (THR and TKR). Analyses of large databases were conducted using various data sources: a systematic literature review; a direct data analysis from The Functional Outcomes Research for Comparative Effectiveness in Total Joint Replacement and Quality Improvement Registry (FORCE-TJR) and the Kaiser Permanente Implant Registry (KPIR); and claims data analyses from longitudinal discharge data in New York and California states. The literature review included U.S. patients (≥18 years) who received THR or TKR for primary end-stage osteoarthritis and prospectively collected data on patient-reported outcome measures (PROMs) from at least 100 subjects and/or 2-year implant survival for at least 250 implants. Random effects models were used for meta-analysis. Data were available from a total of 951 100 patients. After screening of 7979 abstracts, 294 studies underwent full-text review and 31 studies contributed to the evidence synthesis (333 995 implants). Direct data analysis of FORCE-TJR contributed 9223 joint replacement patients to the construction of OPC for effectiveness; KPIR contributed 262 044 patients for the construction of OPC for safety. Claims database analysis contributed 345 838 patients to the construction of safety OPC. OPC for safety were constructed for cumulative incidences of 2-year all-cause and septic revision (THR/TKR 2.0%/1.6% and 0.6%/0.7%), and OPC for effectiveness were constructed based on four disease-specific and three general health-related quality of life PROMs (HOOS/KOOS 87.1/80.6; HSS/KSS function 94.4/90.6; SF-12/SF-36, PCS 46.5/41.9, EQ-5D 0.88/0.84). This study is the first to construct a 2-year OPC for the safety and effectiveness of THR and TKR based on U.S. real-world data. Based on these OPC, potential benchmarks for (single-arm study) evaluation of new device innovations are suggested for a regulated and safe introduction to the (commercial) market.